Persistent right aortic arch and associated anatomical anomalies in dogs (Canis lupus familiaris) (Gaceta de Ciencias Veterinarias, 2017)
Persistent fourth right aortic arch is considered one of the most frequent anatomical abnormalities in vascular ring formation. Structure of this type of ring is formed by the aorta originated from the fourth right aortic arch, pulmonary trunk and left arteriosus ligament. Cases described in this study correspond to this type of anomaly, the patients were diagnosed and then underwent surgical treatment to correct the vascular defect. During surgery, the vascular ring observed, which compressed esophagus and trachea. In addition, megaesophagus (cranial to the heart), and presence of a left azygos vein and the formation of connective tissue bands around the esophagus were observed as associated anatomical abnormalities. Left azygos vein was not sectioned because it did not cause esophageal compression in any of cases. These findings coincide with that reported in the literature and reinforce the theory that this type of vascular ring is the most frequent.
Keywords: Right aortic arch; vascular ring; esophagus; dog